Stylistic And Pragmatic Functions Of Clichés In English And Uzbek News Discourse (Texas Journal of Philology, Culture and History, 2025)
This paper investigates the stylistic and pragmatic roles that clichés play in English and Uzbek news discourse. Clichés, while often criticized as overused or unimaginative, serve functional purposes in journalistic communication such as simplifying complex issues, conveying shared values, and reinforcing ideological perspectives. Through a comparative analysis of English and Uzbek news articles, this study reveals both universal and culturally specific uses of clichéd language. The findings highlight the impact of clichés on discourse tone, reader engagement, and message framing.